2012
DOI: 10.1155/2012/872169
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofCandidaSpecies Associated with Vulvovaginal Candidiasis by Multiplex PCR

Abstract: Background. Vulvovaginal candidiasis is a common infection. The aim of this study was to identify the species of vaginalCandidaisolates by using multiplex PCR technique.Methods. 191 isolates from patients admitted to Mahdieh hospital were identified. The vaginal swab specimens were cultured on Sabouraud Dextrose Agar. The ITS1 region between the 18S and 5.8S rRNA genes and a specific DNA fragment within the ITS2 region wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 30 publications
1
36
0
4
Order By: Relevance
“…Candida spp, most commonly C. albicans is a commensal of the vaginal flora in 20%-50% of women, but there has been an increasing trend in isolation of C. glabrata, C. krusei, C. parapsilosis from patients with symptomatic vulvovaginitis and their increasing resistance to commonly used antifungal drugs [5]. In this context, C. auris isolated in this patient and the association with drug resistance and virulence traits hints towards its increasing pathogenicity.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Candida spp, most commonly C. albicans is a commensal of the vaginal flora in 20%-50% of women, but there has been an increasing trend in isolation of C. glabrata, C. krusei, C. parapsilosis from patients with symptomatic vulvovaginitis and their increasing resistance to commonly used antifungal drugs [5]. In this context, C. auris isolated in this patient and the association with drug resistance and virulence traits hints towards its increasing pathogenicity.…”
Section: Discussionmentioning
confidence: 81%
“…The isolate grew at 42°C but failed to grow at 45°C. Due to unavailability of automated methods and a known confirmatory method, molecular identification methods by amplifying a conserved portion of 18SrDNA region, adjacent ITS1and a portion of the 28SrDNA were performed,as described elsewhere [5]. On visualization, a band of approximately 479 bp (which was slightly lower than that for C. glabrata) was seen ( Figure 2).…”
Section: Case Reportmentioning
confidence: 99%
“…Reports have suggested that approximately 75% of women over 25 years of age complain of at least one episode of physician-approved vulvovaginal candidiasis (VVC) during their lifetime, with at least 5% of these cases recurring at least 4 times in a oneyear period. However, asymptomatic microorganism colonization can occur in 25 to 50% of the cases (Mahmoudi Rad et al, 2012;Mascarenhas, et al, 2012). Candida albicans is the most common and clinically relevant pathogen that is responsible for 85-90% of the VVC cases (Mahmoudi Rad et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, asymptomatic microorganism colonization can occur in 25 to 50% of the cases (Mahmoudi Rad et al, 2012;Mascarenhas, et al, 2012). Candida albicans is the most common and clinically relevant pathogen that is responsible for 85-90% of the VVC cases (Mahmoudi Rad et al, 2012). However, other species of Candida, including Candida dubliniensis, Candida glabrata, Candida krusei, and Candida parapsilosis, have been the focus of increasing research over the past few years, due to the development of resistance to first line antifungal treatment strategies (Tortorano, et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Candida albicans is responsible for 65-90% of vaginal Candida species infections, and non-albicans Candida species are responsible for up to 30%. [10][11][12] Trichomoniasis is the most common curable sexually transmitted infection in the world. 1 The Centers for Disease Control and Prevention recommends use of molecular tests for diagnosis.…”
mentioning
confidence: 99%